Social Integration and Domestic Violence Support in an Indigenous Community: Women’s Recommendations of Formal Versus Informal Sources of Support - Gauthier, G. Robin (Journal of interpersonal violence, 2021)
Throughout North America, indigenous women experience higher rates of intimate partner violence and sexual violence than any other ethnic group, and so it is of particular importance to understand sources of support for Native American women. In this article, we use social network analysis to study the relationship between social integration and women’s access to domestic violence support by examining the recommendations they would give to another woman in need. We ask two main questions: First, are less integrated women more likely to make no recommendation at all when compared with more socially integrated women? Second, are less integrated women more likely than more integrated women to nominate a formal source of support rather than an informal one? We use network data collected from interviews with 158 Canadian women residing in an indigenous community to measure their access to support. We find that, in general, less integrated women are less likely to make a recommendation than more integrated women. However, when they do make a recommendation, less integrated women are more likely to recommend a formal source of support than women who are more integrated. These results add to our understanding of how access to two types of domestic violence support is embedded in the larger set of social relations of an indigenous community.